Keterawetan dan Ketahanan Enam Jenis Kayu yang Diawetkan dengan CKB terhadap Rayap Tanah dan Bubuk Kayu Kering Treatability and Durability of Six Wood Species Treated by CKB Against Subterranean Termite and Powder Post Beetle - Mohammad Muslich; Jasni Jasni (Jurnal Ilmu dan Teknologi Kayu Tropis, 2004)
This paper discusses a study on the treatability and durability of six wood species treated by CKB preservative by full cell process against subterranean termite and powder post beetle. Six wood species measuring 5 cm by 5 cm by 60 cm were treated with 7% CKB preservative by full cell process for 1 hour, 2 hours and 4 hours in 150 psi. The treated and untreated wood samples were tested against subterranean termite and powder posts beetle for 8 months. The results of the study indicated that full cell process with CKB were able to prevent insect attack. Untreated woods specimens were susceptible to subterranean termite and powder post beetle attack. The results, after taking both retention and penetration showed that sengon (Paraserianthes falcataria (L.) Nielsen) were permeable; while cempaka (Elmerillia ovalis Dandy), surian (Toona sureni Merr.) and durian (Durio zibethinus Merr.) were moderately resistant. While mersawa (Anisoptera costata Korth.) and Palado (Aglaia sp.) were extremely resistant